Locating the university lecture as a contemporary educational practice - Crook Charles (Journal of China Computer-Assisted Language Learning)
The university lecture has attracted much critical evaluation over a long period. Yet it remains resilient in the face of such scepticism. However, the project reported here finds that a sample of experienced lecturers fail to recognise the terms of this critique in their own practice. They uniformly describe contrary approaches. These are characterised in terms of three communication priorities: orchestration, enactment, and dialogue. An emphasis on the dialogic nature of exposition suggested an exploratory intervention in which students collaborated with a peer around a recorded lecture. Transcripts of these sessions indicate the way in which lectures can prompt a ‘conversational’ reaction within their audiences. The overall pattern of findings reported here helps to interpret the resilience of the live lecture. The success of online courses implies that lecturing co-presence is central to the resilience of lecturing in mainstream education. This is interpreted in relation to practitioners’ continued protection of three imperatives within live exposition: community, conviviality and conversation.